PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN RESORT AND SPA BALI - Jecky Mahendra; Kasmita kasmita (Universitas Negeri Padang, 2020)
This research starts from the writer's observation of the performance evaluation and training activities that have not been perfectly done. The author discusses several problems, namely: performance targets provided by management have not been achieved, employee performance has decreased, training schedules are not fully realized, there are still employees who do not follow the planned training. The purpose of this research is to analyze the effect of training on employee performance of AYANA Resorts and Spa BALI. The urgency of this research is to find out the effect of training on employee performance, if problems regarding AYANA Resorts and Spa BALI employees continue to have a serious impact on the work of employees who are not in accordance with the expectations of guests and also the management of AYANA Resorts and Spa BALI. This will result in a bad image of the hotel and a reduction in guests staying at AYANA Resorts and Spa BALI. This type of research is classified in quantitative research with a causal associative approach, the population in this study is all operational employees at AYANA Resort and Spa BALI with a total of 181 people with the sampling technique is purposive sampling totaling 65 people. The training variable data collection technique is carried out by distributing questionnaires (questionnaire) using a Likert scale method that has been tested for validity and reliability, while employee performance data is obtained from HRD. Then the data were analyzed through simple linear regression analysis with the help of SPSS version 20.00. Based on the results of research conducted, the following results are obtained: (1) Training at AYANA Resort and Spa BALI shows enough categories with a percentage of 46.62%, (2) Employee performance at AYANA Resort and Spa BALI, included in both categories with a percentage of 55.38%, (3) Based on the results of the hypothesis test, an R Square value of 0.069 was obtained, meaning that the influence of the training variable on employee performance variables was 6.9% while 93.1% was influenced by other factors. Then obtained a regression coefficient of 0.171 with a significance of 0.034 <0.05. This means that each increase of 1 training unit will increase 0.171 employee performance units. So the hypothesis in this study is Ha is accepted H0 is rejected.